New approach shows no association between maternal milk fatty acid composition and childhood wheeze or asthma. Issue 9 (11th April 2017) - Logan, C. A.; Brandt, S.; Wabitsch, M.; Brenner, H.; Wiens, F.; Stahl, B.; Marosvölgyi, T.; Decsi, T.; Rothenbacher, D.; Genuneit, J.
Abstract: Background: Previous observational studies have implied breastmilk fatty acid composition may play a role in the development of atopic eczema or atopic sensitization in breastfed infants and toddlers. However, studies investigating associations with wheeze and asthma in later childhood are scarce and did not account for inherent correlation of compositional data. Our aim was to explore the association of maternal milk fatty acid composition with childhood wheezing phenotypes and asthma up to age 13 years using a new statistical approach. Methods: Breastmilk was collected 6 weeks and 6 months postdelivery in the Ulm Birth Cohort Study (n=720 and n=454, respectively). Concentrations of 28 fatty acids were measured by high‐resolution capillary gas‐liquid chromatography. To control for constant‐sum constraint, concentration data were transformed using the centered log ratio method. Compositional biplots and correlation matrices were used to group centered log ratio transformed fatty acids. Adjusted risk ratios with parent‐reported wheezing phenotypes and doctor‐diagnosed asthma were computed using a modified Poisson regression. Results: We observed no straightforward evidence of associations between overall breastmilk fatty acid composition and specific wheeze phenotypes or doctor‐diagnosed asthma. Conclusion: Using appropriate statistical methodology, we report null associations. These findings may partly be attributable to several cohort‐specific factors associated with breastfeeding and breastmilk collection. Further studies could improve on ours by analyzing samples of breastmilk and formula and by including all children for whom these are exclusively or together the major source of fatty acids in the first months of life.